Computación Cuántica Aplicada en Criptografía (2018)
This document contains information about the advances that have been developed in recent years on quantum computing in the field of cryptography. It covers topics such as quantum authentication schemes, the operation of the RSA encryption algorithm, how this algorithm is analyzed to violate it and how quantum computing performs its violation thanks to the Shor algorithm, with an example developed in Java.